Badania jakościowe w glottodydaktyce. Analiza ilościowa badań prezentowanych na łamach „Neofilologa” (2012–2021) - Smuk, Maciej (Neofilolog, 2023)
The article is devoted to the application of qualitative research in glottodidactics. In the first part of the text I recall the features of qualitative orientation, and then I present recommendations for the use of some methods and techniques: observation (self-observation, learner diary), interviews (focus groups), questionnaires. Other methods – narrative research, didactic dialogue, duoethnography, etc. – are only mentioned at the end. In the second part, I present the qualitative projects that were published in the journal “Neofilolog” in 2012–2021. Several aspects are analyzed: research methods/techniques used, research groups, specific methodological tendencies, topics and issues of the research. In the conclusion, I answer two questions: what contexts are too rarely studied and what types of research are missing.